2014
DOI: 10.1016/s0140-6736(14)60892-8
|View full text |Cite
|
Sign up to set email alerts
|

Body-mass index and risk of 22 specific cancers: a population-based cohort study of 5·24 million UK adults

Abstract: SummaryBackgroundHigh body-mass index (BMI) predisposes to several site-specific cancers, but a large-scale systematic and detailed characterisation of patterns of risk across all common cancers adjusted for potential confounders has not previously been undertaken. We aimed to investigate the links between BMI and the most common site-specific cancers.MethodsWith primary care data from individuals in the Clinical Practice Research Datalink with BMI data, we fitted Cox models to investigate associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
1,084
10
26

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,401 publications
(1,232 citation statements)
references
References 34 publications
50
1,084
10
26
Order By: Relevance
“…We identified all cancers through medical codes from the CPRD medical dictionary related to cancer (mapped to ICD‐10 chapter 2 headings in a previous study8), and through ICD‐10 codes in the HES, and restricted to first occurrence of cancer. We estimated risk for any cancer combined and for 14 individual cancers; the site‐specific cancer outcomes chosen for analysis included the most common cancers and was further informed by findings from previously published data on pericarditis and cancer risk 4, 9, 10…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified all cancers through medical codes from the CPRD medical dictionary related to cancer (mapped to ICD‐10 chapter 2 headings in a previous study8), and through ICD‐10 codes in the HES, and restricted to first occurrence of cancer. We estimated risk for any cancer combined and for 14 individual cancers; the site‐specific cancer outcomes chosen for analysis included the most common cancers and was further informed by findings from previously published data on pericarditis and cancer risk 4, 9, 10…”
Section: Methodsmentioning
confidence: 99%
“…We used body mass index (BMI) calculated directly from weight and height records (weight/height2) and created 4 categories: underweight (BMI <18.5), normal weight (BMI=18.5–24.9), overweight (BMI=25.0–29.9), and obesity (BMI >30), using World Health Organization (WHO) grouping of overweight and obesity. Details on processing, cleaning, and representativeness of CPRD BMI data have been previously described 8, 11. We categorized smoking status into never‐smoker, current smoker, and ex‐smoker, and similarly alcohol use into never‐use, current use, and ex‐use.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous epidemiological studies confirm an association between obesity and various cancer forms, including EC [9]. This malignancy has also been associated with sedentarism, type II diabetes mellitus, and polycystic ovary syndrome [10e14].…”
Section: Introductionmentioning
confidence: 99%
“…Han et al in a systematic review and meta-analyses observed that that singletons born to underweight women have higher risks of preterm birth (overall, spontaneous and induced) and LBW than those born to women with normal weight (9) BMI provides a reliable indicator of body fat for most people and is used to screen for weight categories that may lead to problems (7) . It is an inexpensive and easy-to-perform method of screening for weight category, for example underweight, normal or healthy weight, overweight, and obesity (10) . The critical relevance of mothers nutritional status was emphasized by the fact that in all the EAG including Assam state, mothers who were underweight were more likely to have LBW babies than normal weight (11) .…”
Section: Discussionmentioning
confidence: 99%